In this moment : a novel - Kingsbury, Karen (Kingsbury, Karen. Baxter family., 2017)
Hamilton High Principal Wendell Quinn wants to see real change in his community, so he starts a voluntary after-school Bible Study and prayer program called Raise the Bar. He knows he is risking his job by leading the program, but before long, Raise the Bar meetings are standing room only. A year later, violence and gang activity are sharply down, test scores are up, and drug use and teen pregnancy have plummeted. The program is clearly working<U+2014>until one parent files a lawsuit, claiming Wendell has violated his daughter's rights. But Principal Quinn knows God is on his side, and he refuses to back down. As he prepares for court, he is deluged by a storm of national attention and criticism. He wants just one attorney on his side in the fight of his life<U+2014>Luke Baxter.